PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA TEMA PEDULI TERHADAP MAHLUK HIDUP KELAS IV SD - Nurfauziah, Nurfauziah; Dinda Yarshal (Bajang Institute, 2024)
This research aims to develop a Contextual Teaching and Learning-Based Student Worksheet that is suitable for use in the thematic learning process on the theme